INOVASI DAKWAH BERBASIS AI DI ERA 5.0: PERSPEKTIF ISLAM KONTEMPORER - MUSLIMIN, MOH. (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2024)
In the era of Industrial Revolution 5.0, technology is increasingly influencing various aspects of life, including the spread of Islamic da'wah. Artificial intelligence (AI) is now a potential tool in bridging the gap between ulama andummah, as well as expanding the reach of da'wah to areas that were previously difficult to reach. However, important questions arise regarding how AI can be aligned with authentic Islamic values without sacrificing the essence of da'wah itself. This research explores AI-based da'wah innovations in the contemporary Islamic context, highlighting current phenomena, such as the use of chatbots for religious guidance, big data analysis to understand religious trends, and the application of AI in online Islamic education. Using a qualitative approach, this research examines the perspectives of ulama, technology experts and the Muslim community regarding the acceptance and ethical challenges faced in applying AI for da'wah. The research results show that AI offers great potential to increase the efficiency and effectiveness of da'wah, however there is an urgent need for strict supervision and guidance so that this technology is used in accordance with Islamic principles. The conclusion of this research emphasizes the need for synergy between technology experts and ulama in developing AI applications that are not only sophisticated but also shariacompliant. Thus, this research provides important insights for historians, da'wah practitioners, and policy makers in designing relevant da'wah strategies in this digital era.